Improving Beginning Reading Ability Through Media Use Sentence Cards Learning for Class II Students at SD Negeri 1 Poka - Gabriel M. E. Nusaaly; Ribka. L. Ririhena; Sarah Sahetapy (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to improve the beginning reading skills of second-grade students at Poka 1 Elementary School through the use of sentence cards. The study used Classroom Action Research (CAR) in two cycles, each consisting of planning, action, observation, and reflection. Twenty students participated in the study. The research instruments included observation, oral tests, interviews, and documentation. The results showed that in the initial test, students' reading ability only reached an average of 42.59% (in the poor category). After the first cycle, the reading ability increased to 47.23% (in the poor category), and in the second cycle, it significantly increased to 73.23% (in the good category). Therefore, it can be concluded that the use of sentence cards can improve the beginning reading skills of second-grade students at Poka 1 Elementary School.